Anti-osteoclastogenic cycloartane saponins from Mussaenda pubescens. Issue 18 (8th September 2022) - Huong, Le Thanh; Thao, Tran Phuong; Trang, Do Thi; Lee, Jeong-Hyung; Tai, Bui Huu; Kiem, Phan Van; Nhiem, Nguyen Xuan; Dang, Nguyen Hai
Abstract: The methanolic extract of Mussaenda pubescens Dryand leaves exhibited significant anti-osteoclastogenic activity. Chemical investigation of M. pubescens led to the isolation of one new cycloartane saponin, mussaendoside X (1 ) along with eight known compounds: heinsiagenin A 3- O -[ α -L-rhamnopyranosyl-(1→2)- O - β -D-glucopyranosyl-(1→2)]- O - β -D-glucopyranoside (2 ), mussaendoside O (3 ), heinsiagenin A 3- O -[ α -L-rhamnopyranosyl-(1→2)- O - β -D-glucopyranosyl-(1→2)]- O - β -D-glucopyranosyl-(1→4)- O - β -D-glucopyranoside (4 ), mussaendoside G (5 ), mussaendoside U (6 ), shanzhiside methyl ester (7 ), barlerin (8 ) and musaenoside (9 ). Their structures were elucidated by extensive spectroscopic methods including 1D- and 2D-NMR as well as MS analysis and comparison with the literature. Cycloartane saponins 1 –6 positively suppressed osteoclast formation in an anti-osteoclastogenic screening assay. Consequently, treatment of RANKL-stimulated RAW 264.7 cells with compounds 1 –4 significantly decreased the number of osteoclasts in a concentration-dependent manner. Six compounds from M. pubescens, with the new cycloartane, mussaendoside X, were shown for the first time as potential effective inhibitors of osteoclastogenesis. Graphical Abstract: UF0001